Adjuvant potential of resiquimod with inactivated Newcastle disease vaccine and its mechanism of action in chicken. Issue 36 (26th August 2015) - Sachan, Swati; Ramakrishnan, Saravanan; Annamalai, Arunsaravanakumar; Sharma, Bal Krishan; Malik, Hina; Saravanan, B.C.; Jain, Lata; Saxena, Meeta; Kumar, Ajay; Krishnaswamy, Narayanan
Highlights Resiquimod (R-848) showed potential adjuvant capacity with Newcastle disease (ND) vaccine in SPF chicken. R-848 enhanced antigen specific humoral as well as cellular immune responses. R-848 up-regulated the expression of IFN-α, IFN-β, IFN-γ, IL-4, IL-1β, MHC-II and iNOS transcripts in the chicken spleen. R-848 potentiated the protection capacity of inactivated ND vaccine against virulent ND virus challenge.